Social Anglicanism and Empire: C. F. Andrews's Christian Socialism - Lockley, Philip J. (Studies in church history, 2018)
Charles Freer Andrews (1871-1940) was a close friend of Mohandas K. Gandhi and played a celebrated role in the Indian struggle for independence within the British empire. This article makes the case for understanding Andrews as a pioneering example of the evolution from nineteenth-century Christian Socialism to twentieth-century global ‘social Anglicanism’, as Andrews's career fits a form better recognized in later campaigners. The article draws attention to three beliefs or principles discernible in Andrews's life as a Christian Socialist in the 1890s: the incarnation as a doctrine revealing the brotherhood of humanity; the Church's need to recognize and minister to the poor; and the Church's call to send out its adherents to end ‘social abuses’ and achieve ‘moral victories’. These three core Christian Socialist beliefs were applied in Andrews's thought and achievements during the second half of his life, in the colonial contexts of India, South Africa and Fiji. By comparing his thought and activity with perceptions of empire traceable among contemporary Anglican Christian Socialists, Andrews's colonial career is found to have enabled Anglican social thought to take on a global frame of reference, presaging proponents of an Anglican global social conscience later in the century.